Ecology of Faunal Communities on the Andaman and Nicobar Islands - Venkataraman, K.; Raghunathan, C.; Sivaperuman, C. (Springer Berlin Heidelberg : Imprint: Springer, 2012)
The Andaman and Nicobar Islands, India, consist of 572 islands with a land area of 8,249 km2. Their topography is hilly and undulating, with elevations up to 732 m on the Andaman and up to 568 m on the Nicobar Islands. They are known for their rich biodiversity and a very high degree of endemicity in all taxa, especially in plants, reptiles, fishes and corals. Their habitats include bays, mangroves, moist deciduous forests and evergreen forests. Comprising 20 chapters each written by an expert or professional in his/her particular field this book offers new insights into the fascinating faunal communities of these islands and provides the fundamentals for their conservation and environmental management.